Tumor evolution selectively inactivates the core microRNA machinery for immune evasion - Song, Tian-Yu; Long, Min; Zhao, Hai-Xin; Zou, Miao-Wen; Fan, Hong-Jie; Liu, Yang; Geng, Chen-Lu; Song, Min-Fang; Liu, Yu-Feng; Chen, Jun-Yi; Yang, Yu-Lin; Zhou, Wen-Rong; et al. (Nature communications, 2021)
Cancer cells acquire genetic heterogeneity to escape from immune surveillance during tumor evolution, but a systematic approach to distinguish driver from passenger mutations is lacking. Here we investigate the impact of different immune pressure on tumor clonal dynamics and immune evasion mechanism, by combining massive parallel sequencing of immune edited tumors and CRISPR library screens in syngeneic mouse tumor model and co-culture system. We find that the core microRNA (miRNA) biogenesis and targeting machinery maintains the sensitivity of cancer cells to PD-1-independent T cell-mediated cytotoxicity. Genetic inactivation of the machinery or re-introduction of ANKRD52 frequent patient mutations dampens the JAK-STAT-interferon-γ signaling and antigen presentation in cancer cells, largely by abolishing miR-155-targeted silencing of suppressor of cytokine signaling 1 (SOCS1). Expression of each miRNA machinery component strongly correlates with intratumoral T cell infiltration in nearly all human cancer types. Our data indicate that the evolutionarily conserved miRNA pathway can be exploited by cancer cells to escape from T cell-mediated elimination and immunotherapy. Dysregulation of the microRNA machinery has crucial roles in cancer development. Here the authors show that inactivation of proteins involved in microRNA-mediated gene silencing, such as ANKRD52 or AGO2, confers resistance to T cell-mediated immune response in a preclinical cancer model.